2014
DOI: 10.1088/0253-6102/61/4/17
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Controlled Transparent Superluminal Light Propagation in a Doppler-Broadened Four-Level N-Type System

Abstract: Abstract. The propagation of a weak probe field in a four-level N-type quantum system in the presence of spontaneously generated coherence (SGC) is theoretically investigated. The optical properties of the system are studied and it is shown that the group velocity of light pulse can be controlled by relative phase of applied fields. By changing the relative phase of applied fields, the group velocity of light pulse changes from transparent subluminal to the transparent superluminal light propagation. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It is well known that the optical properties of a closedloop atomic system interacting with laser fields are completely phase-dependent [29][30][31][32]. The phase-dependent behaviour can be also induced by quantum interference due to spontaneous emission of an atom with two closely lying levels [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Such coherence can be created by the interference of spontaneous emission, called spontaneously generated coherence (SGC), of either a single excited level to two close-lying atomic levels [34] or two close-lying atomic levels to a common atomic level [35].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the optical properties of a closedloop atomic system interacting with laser fields are completely phase-dependent [29][30][31][32]. The phase-dependent behaviour can be also induced by quantum interference due to spontaneous emission of an atom with two closely lying levels [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Such coherence can be created by the interference of spontaneous emission, called spontaneously generated coherence (SGC), of either a single excited level to two close-lying atomic levels [34] or two close-lying atomic levels to a common atomic level [35].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the optical properties of a four-level N-type quantum system have been extensively studied [37][38][39][40][41][42]. For instance, resonance fluorescence, squeezing and absorption spectra of a laser-driven N-type system was investigated and it was demonstrated that quantum interference can induce two prominent and nearly transparent holes where the slope of the refractive index is very steep [39].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, resonance fluorescence, squeezing and absorption spectra of a laser-driven N-type system was investigated and it was demonstrated that quantum interference can induce two prominent and nearly transparent holes where the slope of the refractive index is very steep [39]. Propagation of a weak probe field in a four-level N-type quantum system in the presence of spontaneously generated coherence (SGC) was theoretically investigated and found that group velocity of light pulse can be controlled by relative phase of applied fields [42]. Though the above-mentioned effects have been studied in the system, only a few studies have been performed on its quantum entangled properties and to the best of our knowledge, the maximal atom-photon entanglement in such system have not been achieved previously.…”
Section: Introductionmentioning
confidence: 99%